Unpacking civil society sustainability: looking back, broader, deeper, forward. Issue 5 (3rd July 2016) - Hayman, Rachel
ABSTRACT: More evidence is emerging about challenges many different types of civil society organisations around the world are facing relative to the sustainability of their organisations and functions. Valuable experiences and lessons are also emerging of how organisations are responding. This concluding article brings together themes from across the articles in this special issue, offering a broad understanding of civil society sustainability, exploring why this matters in the present geopolitical context, reviewing what has changed from previous analyses, and proposing ideas for what needs to change as we move forward.